6p^2 -5p -6

## Factor the trinomial completely

Tutors, please sign in to answer this question.

# 2 Answers

Hi Paula,

6p²-5p-6 = 6p²-9p+4p-6

=3p(2p-3)+2(2p-3)

=(3p+2)(2p-3)

The solutions are

3p+2=0

p=-2/3

2p-3=0

p=3/2

by finding D = b^2-4*a*c , you can check whether the above equation is easily factorable.

D=169, which is a perfect square, which means a factor able equation

Using a quadratic equation, you can easily find out p = 18/12 or p=-8/12. Therefore,

6p^2-5p-6=(2p-3)(3p+2)

## Comments

Comment